Impact of Effective Entrepreneurship and Strategic Management on Business Success: An Empirical Study of SMEs in Malaysia (Global Journal of Management and Business Research, 2018)
Abstract not found
Keywords: strategy; strategic management; entrepreneurship; small and medium-sized enterprise; success; internationalization; malaysia